CHARACTER EDUCATION IN DISRUPTIVE ERA IN BOARDING SCHOOLS (MULTI-CASE STUDIES AT ISLAMIC SENIOR HIGH SCHOOL (MA) HUBULO, ISLAMIC SENIOR HIGH SCHOOL (MA) AL-HUDA AND INTEGRATED SENIOR HIGH SCHOOL (SMAT) WIRA BHAKTI GORONTALO) - Annisa Nuraisyah Annas; Ansar; Arwildayanto; Sitti Roskina (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2023)
This research examines character education in the disruptive era in boarding schools. The research uses a qualitative research method with a multi-case design. Research data obtained through interviews, documentation and observation. The data collected is tabulated and analyzed to find out programs and innovations in implementing character education carried out at boarding schools. The results of the research indicate that the character values developed refer to the vision and mission then the school innovate character education strengthening programs, namely (a) innovation of character education planning models with systemic-integrative models. (b) innovation of exemplary implementation models, integration of activities character education in learning and supported by management of a conducive environment in the implementation of strengthening character education in the disruptive era. (c) supervisory model with managerial internal control through order and supervision by involving all related elements. The innovation of character education programs in the disruptive era at boarding schools has positive implications for the character values of students.